Pengaruh Variasi Temperatur Proses Pirolisis terhadap Karakteristik Biopelet Berbahan Baku Arang Limbah Ampas Tebu dan Kulit Kopi - Naufal Dwi Qurniawan; Arif Rahman Saleh; Rany Puspita Dewi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Increasing in energy demand and limited fossil fuel reserves have driven the use of environmentally friendly alternative energy sources. This study aims to analyze the effect of pyrolysis temperature variations on the quality of biopellets made from bagasse and coffee husks. The materials were prepared in a 50:50 ratio with the addition of 15% tapioca flour as a binder. The pyrolysis process was carried out at temperatures of 450°C, 500°C, and 550°C for 120 minutes in oxygen-free conditions. The biochar resulting from pyrolysis was formed into biopellets, which were then tested for proximate composition, calorific value, and combustion rate. The results showed that an increase in pyrolysis temperature had a significant effect on the characteristics of the biopellets. A temperature of 550°C produced the lowest moisture content (8.436%), the highest fixed carbon content (62.191%), the highest calorific value (6293 cal/g), and the highest combustion rate (0.05789 g/sec). Conversely, ash content increased with rising temperature, while volatile matter content decreased. Thus, the best biopellets were obtained at a temperature of 550°C. This study confirms the potential of bagasse and coffee husks as raw materials for biopellets through pyrolysis temperature optimization to support the development of sustainable biomass energy.